The Effect of Murabahah and Mudharabah Financing of Return on Equity (Case Study of Sharia Bank in Indonesia for 2013-2019) - Ahnaf Taqiy Robbani; Irvan Yoga Pardistya (Institute of Computer Science (IOCS), 2020)
This study aims to examine the effect of murabahah and mudharabah financing on return on equity in Indonesia from 2013-2019. This research method uses descriptive verification method with a quantitative approach. The data used in this study comes from the financial statements of sharia bank companies in Indonesia for the period 2013-2019. This type of research is a time series. Then, the data that has been obtained will be analyzed using multiple linear regression analysis and hypothesis testing consisting of the t test and f test with the help of SPSS 21 software. The sampling technique uses non probability sampling with purposive sampling technique. Based on the research results, it can be seen that the development of Murabahah financing in sharia banking in Indonesia has fluctuated every year. Meanwhile, developments in Mudharabah financing have fluctuated almost as a whole every year. Likewise, with the benefits, which fluctuates every year. The results of statistical testing show that partially Murabahah Financing has a positive effect on Return On Equity (ROE) and Mudharabah has no effect on Return On Equity (ROE). Meanwhile, simultaneously Murabahah and Mudharabah Financing has an effect on Return On Equity (ROE). Meanwhile, the coefficient of determination (R2) was 47.2%. This shows that the Murabahah and Mudharabah Financing variables can affect the Return On Equity by 47.2% and the remaining 52.8% is influenced by other variables which are not used in this study.